Changes in Physicochemical Properties, Volatile Profiles, and Antioxidant Activities of Black Apple During High-Temperature Fermentation Processing - Zhu, Zuoyi; Zhang, Yu; Wang, Wei; Sun, Suling; Wang, Junhong; Li, Xue; Dai, Fen; Jiang, Yunzhu (Frontiers in Nutrition, 2022)
Black apple is a new elaborated product obtained from whole fresh apple through fermentation at controlled high temperature (60~90 °C) and humidity (relative humidity of 50~90%). The appearance, color, texture and taste of black apple changed dramatically compared with fresh apple. In this study, changes in the physicochemical and phytochemical properties, volatile profiles and antioxidant capacity of apple during the fermentation process were investigated. Results showed that the browning intensity and color difference increased continuously during the whole 65-day fermentation process (p<0.05). Sugars decreased in the whole fermentation process (p<0.05), whereas the contents of organic acids increased first, and then decreased with prolonged 35 days of fermentation (p<0.05). Total polyphenol content of black apple showed an increase of 1.5-fold as that of fresh apple, whereas 12 common polyphenolic compounds present in fresh apple decreased dramatically in the whole fermentation process (p<0.05). The analysis of flavor volatiles showed that high-temperature fermentation decreased the alcohols and esters levels, and resulted in the formation of furanic and pyranic compounds, as the main products of Maillard reaction. Antioxidant activities of black apple were enhanced compared with fresh apple and results indicated that the enhancement of antioxidant activities was related to the polyphenols and products of Maillard reaction.